Amalgamated fiber/hydrogel composites based on semi-interpenetrating polymer networks and electrospun nanocomposite fibrous mats. (5th November 2020) - Papaparaskeva, Georgia; Louca, Maria; Voutouri, Chrysovalantis; Tanasă, Eugenia; Stylianopoulos, Triantafyllos; Krasia-Christoforou, Theodora
Graphical abstract: Highlights: Synthesis and characterization of amalgamated fiber/hydrogel 3D composites. Investigation of materials' mechanical properties under unconfined compression. Enhanced mechanical performance via fiber inclusion within the hydrogels. Dependence of the mechanical properties on the fiber dispersion mode. Τhe 3D fiber/hydrogel composites showed in vitro biocompatibility. Abstract: Amalgamated 3D fiber/hydrogel composites were successfully synthesized based on double-hydrophilic semi-interpenetrating (semi-IPN) hydrogel matrices consisting of 1, 2-bis-(2-iodoethoxy)ethane (BIEE)-crosslinked poly(2-(dimethylamino)ethyl methacrylate) (pDMAEMA) chains and linear polyvinylpyrrolidone (PVP), and prefabricated PVP/Ag nanocomposite electrospun fibrous mats. The latter were incorporated within the semi-IPN hydrogels by following 2 unique ways of dispersion, i.e. the "laminated" and the "homogeneous" dispersion mode. In the "laminated" dispersion mode, the prefabricated electrospun fibrous mat was placed in the circumference of the fiber/hydrogel composite, while in the "homogeneous" dispersion mode, 2D circular fibrous mats were homogeneously encapsulated within the 3D hydrogel matrix. Among others, the effect of fiber inclusion as well as of the fiber dispersion mode within the hydrogel matrix on the materials' mechanical properties was investigated. The obtained results clearly demonstrated that the dispersion mode of electrospun fibrous mats within the hydrogel influences significantly the mechanical performance of the resulting composites. Moreover, the influence of the presented structure-defined 3D fiber/hydrogel composites on the viability of human pancreatic fibroblasts was investigated in vitro . Consequently, these fiber/hydrogel composites exhibiting enhanced mechanical performance and biocompatibility could be potentially used as tissue engineering scaffolds with controllable mechanical properties and multi-functionalities.